Advances in electrocardiology, 2004 : proceedings of the 31st International Congress on Electrocardiology, Kyoto, Japan, 27 June-1 July 2004 - Hiraoka, Masayasu, 1940- (World Scientific, 2005)
Electrocardiology has witnessed a century of development since the introduction of Einthoven's Galvanometer. With rapid progress in the scientific, technological and clinical aspects of the field of electrocardiology in recent years, electrocardiology now covers a wide range of topics from molecules as the electrical origin of the heart to diagnostic and therapeutic applications for cardiovascular diseases. This volume presents the latest information and developments in the field, from basic science to clinical electrocardiology. A wide range of topics are covered, including molecular biology.